2021
DOI: 10.1002/solr.202100487
|View full text |Cite
|
Sign up to set email alerts
|

True Cost of Solar Hydrogen

Abstract: Green hydrogen will be an essential part of the future 100% sustainable energy and industry system. Up to one‐third of the required solar and wind electricity would eventually be used for water electrolysis to produce hydrogen, increasing the cumulative electrolyzer capacity to about 17 TWel by 2050. The key method applied in this research is a learning curve approach for the key technologies, i.e., solar photovoltaics (PV) and water electrolyzers, and levelized cost of hydrogen (LCOH). Sensitivities for the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 46 publications
1
78
0
Order By: Relevance
“…Global-local analyses for hybrid PV-wind based green Hydrogen indicates huge and lowcost upcoming Hydrogen potential all over the world [85]. Latest cost-optimized green Hydrogen for large utility-scale applications indicates that there is cost parity of green Hydrogen and SMR H 2 for the best solar resource regions and broad cost parity is expected worldwide by 2030 [86]. Furthermore, electrolyzer cost competitiveness is largely limited by policy obstacles that prevent electrolyzer participation in the wholesale electricity market [87].…”
Section: Statements In the Seibert-rees (S-r) Paper And Counter-argumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Global-local analyses for hybrid PV-wind based green Hydrogen indicates huge and lowcost upcoming Hydrogen potential all over the world [85]. Latest cost-optimized green Hydrogen for large utility-scale applications indicates that there is cost parity of green Hydrogen and SMR H 2 for the best solar resource regions and broad cost parity is expected worldwide by 2030 [86]. Furthermore, electrolyzer cost competitiveness is largely limited by policy obstacles that prevent electrolyzer participation in the wholesale electricity market [87].…”
Section: Statements In the Seibert-rees (S-r) Paper And Counter-argumentsmentioning
confidence: 99%
“…Section 3.1.12, "The Liquid Fuels Question" claims that "it is highly unlikely that synthetic liquid fuel substitutes for FFs [fossil fuels] can be produced sustainably in any more than small quantities for niche applications". Vast literature has been published in recent years on e-fuels and e-chemicals, such as green Hydrogen [85,86,163], e-Methane [164,165], Fischer-Tropsch fuels [166,167], e-Ammonia [168,169] and e-Methanol [170,171], all showing that electricity-based fuels are in reach. In a global energy system transition analysis reaching 100% RE in 2050 [46], with 90% electricity share in primary energy (mainly PV, wind and some hydropower) and strong growth in energy service demands, it has been shown that the total energy system cost can be kept at present levels, while the overall energy system efficiency can be increased by a factor of two [46], mainly due to the phase-out of combustion processes which can be substituted by direct electricity-based processes.…”
Section: Statements In the Seibert-rees (S-r) Paper And Counter-argumentsmentioning
confidence: 99%
“…In the literature, various techno‐economic studies of hydrogen production from solar energy can be found. [ 6–12 ] Broadly speaking, they can be classified into three categories: 1.Modelling of state‐of‐the‐art technologies to obtain an estimate for the current LCOH 2 [ 6,11 ] …”
Section: Introductionmentioning
confidence: 99%
“…In the literature, various techno-economic studies of hydrogen production from solar energy can be found. [6][7][8][9][10][11][12] Broadly speaking, they can be classified into three categories:…”
mentioning
confidence: 99%
See 1 more Smart Citation